Mengenali Potensi: Asesmen Psikologi Bakat, Minat, dan Kepribadian untuk Pengembangan Potensi Siswa di SD Ciherang, Jawa Barat - Fahlevi, Reza; Zamralita, Zamralita; Basaria, Debora; Dewi, Fransisca Iriani Roesmala; Widyastuti, Philomena Esti; Valentine, Raissa (Penerbit Widina, Widina Media Utama, 2025)
Improving the quality of primary education in under-resourced areas such as Ciherang Village, West Java, remains challenging due to limited facilities, guidance, and access to structured psychological assessments. This community engagement program aimed to help students at SD Ciherang recognize their cognitive abilities, interests, and personality traits through a systematic assessment. A total of 53 sixth-grade students participated in three instruments: Raven’s Colored Progressive Matrices (CPM) for cognitive ability, SDS Holland for career interests, and the Big Five Inventory (BFI) for personality traits. The program was implemented using a Community-Based Research (CBR) approach that actively involved teachers and Thematic Community Service (KKNT) students. The results showed that most students had good to very good cognitive abilities. Their dominant interests were Artistic and Social, indicating a strong preference for creativity and social interaction. Personality profiles were primarily characterized by Agreeableness and Extraversion, reflecting cooperative, empathetic, and sociable tendencies. These findings highlight the need for extracurricular programs focusing on arts, social engagement, and leadership, as well as structured activities to develop discipline and self-management skills. This initiative provides tangible contributions in the form of tailored recommendations for extracurricular development based on students’ profiles and offers psychological data as a foundation for school policy planning. The approach is expected to enhance educational services and support the optimal development of students’ potential.ABSTRAKPeningkatan kualitas pendidikan dasar di daerah terbatas seperti Desa Ciherang, Jawa Barat, sering terhambat keterbatasan fasilitas, bimbingan, dan asesmen psikologis yang memadai. Kegiatan pengabdian ini bertujuan membantu siswa SD Ciherang mengenali potensi kognitif, minat, dan kepribadian melalui asesmen terstruktur. Sebanyak 53 siswa kelas VI mengikuti tiga instrumen: Raven’s Colored Progressive Matrices (CPM) untuk kemampuan kognitif, SDS Holland untuk minat karier, dan Big Five Inventory (BFI) untuk kepribadian. Pelaksanaan program menggunakan pendekatan Community-Based Research (CBR) yang melibatkan guru dan mahasiswa KKNT secara aktif. Hasil menunjukkan mayoritas siswa memiliki kemampuan kognitif baik–sangat baik. Minat dominan pada Artistic dan Social, menunjukkan ketertarikan tinggi pada kreativitas dan interaksi sosial, sementara kepribadian siswa didominasi Agreeableness dan Extraversion, yang menggambarkan sifat ramah, kooperatif, dan mudah bersosialisasi. Temuan ini mengindikasikan perlunya pengembangan program ekstrakurikuler seni, sosial, dan kepemimpinan, sekaligus membiasakan kegiatan yang melatih disiplin dan manajemen diri. Kegiatan ini memberikan kontribusi nyata berupa rekomendasi pengembangan program ekstrakurikuler berbasis profil siswa dan menyediakan data profil psikologis sebagai dasar kebijakan sekolah. Pendekatan ini diharapkan meningkatkan layanan pendidikan dan mendukung pengembangan potensi siswa secara optimal.